SmartRock-Based Research on Gyratory Locking Point for Stone Mastic Asphalt Mixture - Zhiqiang Cheng; De Zhang; Shengjia Xie; Pawel Andrzej Polaczyk; Tao Wang (Buildings, 2022)
For gyratory compaction, the concept of the locking point was initially developed to identify the compactability of asphalt mixes and to alleviate potential aggregate crushing in the mold. Most previous studies on the locking point were based on specimens’ height change. Recent studies have indicated that the gyratory locking point of cold mix asphalt mixtures could be determined by the rotation angle range indicator using SmartRock. However, height or rotation angle change ultimately reflects a change in volume. Additionally, there is no clear physical and mechanical connection between the volume change and the gyratory locking point. In this paper, a stone mastic asphalt mixture (SMA 13) was selected for gyratory compaction applying various compaction temperatures. The compaction data were recorded by a SmartRock embedded in different positions. Collected data included stress, rotation angle, and acceleration. The major findings are as follows: (1) the specimen’s locking point could be determined based on a representative stress value when the SmartRock was embedded in the specimen’s center, and the results are close to the traditional evaluation results (LP3 or LP2-2-3); (2) the representative rotation angle value reached a plateau earlier than the representative stress value; (3) the representative acceleration value is not suitable for characterizing the interlocking process during gyratory compaction.